Development and evaluation of a time-resolved fluorescence labelled immunochromatographic strip assay for rapid and quantitative detection of bovine herpesvirus 1 - Liu, Wenxiao; Zhang, Kun; Cheng, Jing; Yu, Shiqiang; Cheng, Chunjie; Jiang, Bo; Zhou, Linyi; Li, Yongqing (Frontiers in Microbiology, 2024)
Bovine herpes virus 1 (BoHV-1) causes a wide variety of diseases in wild and domestic cattle. The most widely used method for viral identification is real-time PCR, which can only be performed in laboratories using sophisticated instruments by expert personnel. Herein, we developed an ultrasensitive time-resolved fluorescence lateral flow immunochromatographic strip (ICS) assay for detecting BoHV-1 in bovine samples using a monoclonal antibody against BoHV-1 labelled with fluorescent microspheres, which can be applied in any setting. The intact process from sample collection to final result can be achieved in 15 min. The limit of detection of the assay for BoHV-1 was 10 2 TCID50/100 μL. The coincidence rate of the ICS method and realtime PCR recommended by the World Organization for Animal Health (WOAH) was 100 % for negative, 92.30 % for positive, and 95.42 % for total, as evaluated by the detection of 131 clinical samples. This detection method was specifically targeted to BoHV-1, not exhibiting cross-reactivity with other bovine pathogens including BoHV-5. We developed an ICS assay equipped with a portable instrument that offers a sensitive and specific platform for the rapid and reliable detection of BoHV-1 in the field. The Point-of-Care test of BoHV-1 is suitable for the screening and surveillance of BoHV-1 in dairy herds.